2021
DOI: 10.2147/ott.s280314
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Receptor Together with PKCα Expression as Prognostic Factors for Astrocytomas Malignancy

Abstract: Introduction: Astrocytomas are the most common and aggressive primary brain tumors, and they are classified according to the degree of malignancy on a scale of I to IV, in which grade I is the least malignant and grade IV the highest. Many factors are related to astrocytomas progression as progesterone receptor (PR), whose transcriptional activity could be regulated by phosphorylation by protein kinase C alpha (PKCα) at the residue Ser400. Our aim was to investigate if PR phosphorylation together with PKCα exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…It should be noted that many authors have demonstrated that the relationship between mRNA expression and protein differs in many cancers. It has been reported in lung cancer and glioblastoma that, for many genes, mRNA expression is lower but protein levels are higher compared with the control [ 50 , 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that many authors have demonstrated that the relationship between mRNA expression and protein differs in many cancers. It has been reported in lung cancer and glioblastoma that, for many genes, mRNA expression is lower but protein levels are higher compared with the control [ 50 , 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytoma malignancies are positively correlated with progesterone receptor (PR) and PKCα levels as well as with the intracellular colocalization of these proteins. Patients with astrocytoma grades III and IV with low expression of PGR and PRKCA mRNA showed higher survival than those with high expression [ 72 ]. Treatment with mTOR inhibitors (rapamycin, temsirolimus, torin-1, and PP242) reduces glioblastoma progression by reducing invasion, migration, and matrix metalloproteinase (MMP) activity (MMP2 and MMP9) through the reduction of PKCα and NF-κB signaling pathways [ 73 ].…”
Section: Pkc Isozymes As Prognostic Biomarkers or Therapeutic Targets...mentioning
confidence: 99%
“…Khalid et al found that the protein content of the PR was higher in GBs (grade IV gliomas) than in grade I and II gliomas from the biopsies of 86 patients [ 54 ]. Recently, Arcos-Montoya et al reported that the PR content, determined with immunofluorescence, was higher in samples derived from patients with GBs than in samples from patients with lower-grade gliomas or normal tissue [ 55 ]. In addition to the positive correlation between protein expression and grade of malignancy in gliomas, there is functional evidence of the PR’s role in the progression of GBs.…”
Section: Role Of Pr and Csrc In Glioblastoma Progressionmentioning
confidence: 99%